TEACHER STRATEGIES IN DEVELOPING A CULTURE OF LITERACY AND NUMERACY IN GRADE V STUDENTS AT MIN 1 MATARAM - A. Basir (Sinar Lima, 2026)
This study aims to determine: 1) teacher strategies in developing a culture of literacy in students, 2) teacher strategies in developing a culture of numeracy in students. The research method used was descriptive qualitative. The subjects studied were the principal, teachers, and grade V students at MIN 1 Mataram. This study used descriptive qualitative research to describe teacher strategies in developing a culture of literacy and numeracy in students. The results showed that: 1) Teacher strategies in developing a culture of literacy include inductive and deductive strategies. The steps in the inductive strategy begin with guidance, habituation, development, and evaluation. In the deductive strategy, the teacher first explains the general meaning of the material, then provides examples or more specific steps. 2) Teachers' strategies for developing a culture of numeracy begin with conditioning the physical environment. Furthermore, in developing a culture of numeracy in students, teachers adapt their strategies to the lesson plans (RPP) to ensure more focused learning. To develop a culture of numeracy, teachers employ three methods: a) problem-based learning (PBL), b) collaborative learning, and c) the Realistic Mathematics Education (RME) method.